Analisis Quality Assurance Penerapan Kebijakan Reward and Punishment Berdasarkan Assesment Tingkat Kepatuhan - Faik Agiwahyuanto; Evina Widianawati; Widya Ratna Wulan; Cesara Kharismaharani Komara (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2020)
Standard Operating Procedure (SOP) for patient registration service at RSUD Dr. M. Ashari Pemalang is in force since 2016. Oversight is carried out in the hospital registration section (outpatient, inpatient, and emergency department) but not documented. This study aims to analyze quality assurance by implementing a reward and punishment policy based on compliance level assessment of inpatient registration service officers in the SOP for patient registration. This research type is descriptive study. Data collected by observation and interview methods. Research subjects were 2 inpatient registration service officers and the Head of the Medical Record Unit. The object of the study was the Standard Operating Procedure for inpatient registration at RSUD Dr. M. Ashari Pemalang. Data analyze using univariate with percentage and content analyze. Research results are RSUD Dr. M. Ashari Pemalang does not have an SOP for Inpatient Registration Services for BPJS patients. Facilities and infrastructure at Inpatient Registration Services are sufficient, but bracelets for baby patients are only available in the emergency room. Another inadequate tool is MNH written manually using white paper. The reward given is only in the form of thank you. Punishment for officers who are not obedient is verbally reprimanded, given input and guidance.